HUBUNGAN TINGKAT STRES DENGAN KEJADIAN PREMENSTRUAL SYNDROME PADA REMAJA PUTRI KELAS VII DI SMPN 01 LUBUK ALUNG - Esti, Amira; Nely, Septa; Azmi, Habibul (Ensiklopedia of Journal, 2024)
Abstract: Premenstrual Syndrome (PMS) is a menstrual disorder in teenagers that occurs in the luteal phase of the menstrual cycle, and is usually felt 7-14 days before menstruation. The most common symptoms are irritability, back pain, and muscle pain or edema. This type of research is research using a descriptive correlation method using a cross sectional study design where variables including risk factors and variables including effects are observed simultaneously at the same time. Researchers conducted an analysis of the relationship between stress levels and events. The population used in this research were all young women in Class VII of SMPN 1 Lubuk Alung, totaling 112 female students. The sample was 88 female students. This research was conducted from 27 to 29 July 2024. Data was collected using a recitation questionnaire, processed using computerization and analyzed using univariate and bivariate analysis.  Univariate results showed that (22.7%) experienced very severe levels of stress, (52.3%) experienced premenstrual syndrome. From the bivariate results based on statistical test results (chi-square), the p value = 0.000 (<0.05) was obtained, which means there is a significant relationship between stress levels and premenstrual syndrome at SMPN 1 Lubuk Alung 2024. Based on the research results, it can be concluded that stress levels can influence premenstrual syndrome at SMPN 1 Lubuk Alung. It is hoped that female students will be able to control excessive stress and do positive things that can reduce stress.Keywords : Stress Level, Premenstrual Syndrome only and teenage girls